2021
DOI: 10.1038/s41598-021-89535-3
|View full text |Cite
|
Sign up to set email alerts
|

Urinary miRNA profiles discriminate between obstruction-induced bladder dysfunction and healthy controls

Abstract: Urgency, frequency and incomplete emptying are the troublesome symptoms often shared between benign prostatic obstruction-induced (BLUTD) and neurogenic (NLUTD) lower urinary tract dysfunction. Previously, using bladder biopsies, we suggested a panel of miRNA biomarkers for different functional phenotypes of the bladder. Urine is a good source of circulating miRNAs, but sex- and age-matched controls are important for urinary metabolite comparison. In two groups of healthy subjects (average age 32 and 57 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Our results suggest that total concentration and size are not indicative of either the presence or progression of Fabry nephropathy. In healthy control subjects, the number of uEVs was reported to be higher in younger subjects [ 41 ]. Specific subpopulations of uEVs or the relationship between them may better reflect pathophysiological changes within the kidney than total uEVs [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that total concentration and size are not indicative of either the presence or progression of Fabry nephropathy. In healthy control subjects, the number of uEVs was reported to be higher in younger subjects [ 41 ]. Specific subpopulations of uEVs or the relationship between them may better reflect pathophysiological changes within the kidney than total uEVs [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression of miR-30b-5p increased over the 10-year period, but only in FD patients without nephropathy. A previous study showed no change in miR-30b-5p expression between young and old control subjects [ 41 ]. Although the role of miR-30b-5p in the kidney was only recently discovered, the expression of miR-30b-5p is thought to have a protective role in podocyte injury [ 30 ] and endothelial-to-mesenchymal transition [ 31 ], which are both important stages in the development of nephropathy in FD.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, they have been shown to have valuable diagnostics potential. They can be relatively easily detected and are used as a part of diagnostics criteria [ 280 ]; they have a potential for early cancer detection [ 287 , 288 ], and they can be obtained from both tissues and body fluids, which allows non-invasive early diagnostics [ 289 , 290 , 291 , 292 , 293 ]. Moreover, they can be used as targets in a specific approach in gene therapy.…”
Section: Future Perspectivementioning
confidence: 99%
“…The molecular changes in BOO might indicate an increasing involvement of miRNAs in the control of bladder function from the overactive to underactive/acontractile states. Thus, mRNA and miRNA might represent markers of detrusor competence (19,20).…”
Section: Atpmentioning
confidence: 99%